2022
DOI: 10.1111/mmi.14894
|View full text |Cite
|
Sign up to set email alerts
|

A conserved Plasmodium structural integrity maintenance protein (SIMP) is associated with sporozoite membrane and is essential for maintaining shape and infectivity

Abstract: Plasmodium sporozoites are extracellular forms introduced during mosquito bite that selectively invade mammalian hepatocytes. Sporozoites are delimited by a cell membrane that is linked to the underlying acto‐myosin molecular motor. While membrane proteins with roles in motility and invasion have been well studied, very little is known about proteins that maintain the sporozoite shape. We demonstrate that in Plasmodium berghei (Pb) a conserved hypothetical gene, PBANKA_1422900 specifies sporozoite structural i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 52 publications
0
6
2
Order By: Relevance
“…PIC5 immunostaining also revealed that the IMC does not underlie the plasma membrane blebs indicating that SIMP depletion leads to loss of contact between the plasma membrane and IMC (Figure 2). This conclusion is indeed supported by their transmission electron microscopic examination of SIMP-depleted salivary gland sporozoites (Singh et al, 2022).…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…PIC5 immunostaining also revealed that the IMC does not underlie the plasma membrane blebs indicating that SIMP depletion leads to loss of contact between the plasma membrane and IMC (Figure 2). This conclusion is indeed supported by their transmission electron microscopic examination of SIMP-depleted salivary gland sporozoites (Singh et al, 2022).…”
mentioning
confidence: 66%
“…The latter observations strongly indicate that the carboxy terminus of SIMP is in fact extracellular. This notion was corroborated by showing that immunostaining with antibodies raised against the carboxy‐terminal part of SIMP also does not require sporozoite permeabilisation (Singh et al, 2022).…”
Section: Figurementioning
confidence: 85%
See 3 more Smart Citations